Exploring the Combination Effect of Cellulase Hydrolysis and Lactobacillus plantarum P‐8 Fermentation on the Textural Properties of Whole Brown Rice - Shiyi Lu; Kaige Li; Qi Su; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Frontiers, 2025)
ABSTRACT Brown rice arouses great attention due to the enriched nutrients, but the unpleasant texture caused by bran layer limits consumer acceptance. To date, although individual enzyme or fermentation treatment has been developed to modify the rice bran, the feasibility of the combination method and co‐effects on whole brown rice have not been investigated. In this study, brown rice treated with cellulase and Lactobacillus plantarum P‐8 together (CAF‐BR) was compared with samples individually treated with cellulase (E‐BR) or fermentation (F‐BR), in terms of cellulase activity, textural attributes, and variations in the main component of brown rice. The results showed CAF‐BR had higher cellulase activity and less glucose in the hydrolysate than E‐BR, reflecting a cooperative effect on rice bran hydrolysis. Moreover, CAF‐BR showed a significantly lower hardness and higher stickiness, compared to E‐BR and F‐BR. This was consistent with the most ruptured bran of CAF‐BR observed by scanning electron microscopy, and the correspondingly highest amount of water absorption ratio, which possibly explained the decreased hardness of CAF‐BR. In addition, the leachates from CAF‐BR possessed the most starch content and the highest content of large molecular weight amylopectin among all samples, which was highly associated with an increased stickiness. Ultimately, this study extends the knowledge about the feasibility of combining enzymatic treatment with fermentation for modifying the wholegrain brown rice, providing a theoretical basis of the cooperative effects on improving the textural properties.